Erosion and its rate on an accumulative Polish dune coast: the effects of the January 2012 storm surge - Tomasz A. Łabuz (Oceanologia)
The Polish coast is a non-tidal area; its shores are affected mainly by autumn-winter storm surges. Those of 6 and 14 January 2012 are representative of the forces driving the erosion of normally accumulative sections of coastal dunes, monitored by the author since 1997. The sea level maximum during these two storm surges reached 1.2 to 1.5 m amsl along the Polish coast. Land forms up to 3 m amsl were inundated. Beaches and low parts of the coast up to this height were rebuilt by sea waves attacking the coast for almost 12 days. Quantitative analyses of the morphological dynamics of the coastal dunes are presented for 57 profiles located along the coast. Only those accumulative sections of the Polish coast are analysed where sand accumulation did occur and led to new foredune development. The mean rate of dune erosion was 2.5 m3 per square metre with an average toe retreat of 1.4 m. Erosion understood as dune retreat was greater when a beach was lower (correlation coefficient 0.8). Dune erosion did not occur on coasts with beaches higher than 3.2 m or on lower ones covered by embryo dunes.